2011
DOI: 10.1186/1471-2458-11-765
|View full text |Cite
|
Sign up to set email alerts
|

Mental ill-health across the continuum of body mass index

Abstract: BackgroundSeveral studies have found a non-linear relationship between mental ill-health and BMI with higher rates in both the underweight and the obese. This study evaluated the shape of the relationship between BMI and distress, suicidal ideation and self-reported mental ill-health conditions in a large population sample.MethodsData were drawn from the South Australian Monitoring and Surveillance System (SAMSS) for the years 2002 to 2009 (n = 46,704). SAMSS monitors population trends in state and national ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 38 publications
2
38
1
2
Order By: Relevance
“…We observed that U-shaped relationships between BMI categories and health are noted in some literature and presented in results but without emphasis [though see 27,34]. Controlling for socioeconomic, health behaviour and deprivation variables, using the Health Survey for England (2006-08), compared with persons of normal weight, we find significantly increased likelihoods of persons to report poor general health for both underweight and obese BMI categories and a slight but significant increase for persons who are overweight.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…We observed that U-shaped relationships between BMI categories and health are noted in some literature and presented in results but without emphasis [though see 27,34]. Controlling for socioeconomic, health behaviour and deprivation variables, using the Health Survey for England (2006-08), compared with persons of normal weight, we find significantly increased likelihoods of persons to report poor general health for both underweight and obese BMI categories and a slight but significant increase for persons who are overweight.…”
Section: Discussionmentioning
confidence: 62%
“…The lack of research into persons of underweight BMI in comparison with those whose BMI is higher than normal weight has been noted [27,34]. This work reveals demographic and health differences between people of different BMI categories and nonlinear associations between BMI and mental health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study including 1,584 young Nigerian adults found no significant correlation between various subsets of anxiety and BMI [23], whereas a symmetrical U-shaped relationship between psychological distress and BMI status was noted in a Mediterranean Spanish population [28]. After controlling for age, Kelly et al only found significantly greater odds of mental illness in the obese and not in the underweight among 46,704 Australian subjects [29]. Hence, while it appears that race may have a modulating effect on the interaction between anxiety and BMI, other variables may play equally important roles including socioeconomic conditions, lifestyle, geographical location, and cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, both military programs and sports programs and physical education activities do not seem to have sufficient intensity and duration to change the BMI of soldiers. The exercises and activities affecting the BMI should be based on Vo 2max and the maximum heart rate and be programmed individually (33). In addition, the BMI is a variable that interacts with several factors, including heredity, physical activity, inflammation, sleep and circadian rhythm, stress, and meals, and cannot be explained only by one factor.…”
Section: Discussionmentioning
confidence: 99%